Pengaruh Daya Tarik Iklan, Pemasaran Digital Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Di Patent Garment Surabaya - Tika Ayu Cindya; Nanis Susanti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The growth of Surabaya's fashion industry increases competition among garment companies. CV. Patent Garment Surabaya needs to understand the factors influencing consumer purchasing decisions. The purpose of this research is to investigate the effects of Advertising Attractiveness, Digital Marketing, and Service Quality on Consumer Purchase Decisions at Patent Garment Surabaya. The population of this study consists of consumers of CV. Patent Garment Surabaya. Sampling was conducted using a survey method with questionnaires, yielding a sample of 100 respondents. Data analysis employed multiple linear regression using SPSS version 22. Results of the Model Suitability Test (F-test) indicate that the research variables are valid. Meanwhile, the Hypothesis Test (t-test) reveals that advertisement appeal and digital marketing positively affect purchasing decisions, albeit insignificantly. Conversely, service quality positively and significantly influences purchasing decisions. The study highlights service quality as a pivotal determinant of consumer purchasing decisions at CV. Patent Garment Surabaya, emphasizing the need for quality enhancement to foster customer satisfaction and loyalty.